1986
DOI: 10.1136/adc.61.7.642
|View full text |Cite
|
Sign up to set email alerts
|

Preschool wheezing and prognosis at 10.

Abstract: SUMMARY Information was collected at birth and at 5 and 10 years of age on the national cohort of children born in one week of April 1970 (the Child Health and Education Study). For 11 465 children, information on wheezing attacks before 5 years was compared with reports of wheezing occurring in the 12 months before the interview at 10 years.Of 2345 children who had had at least one wheezing attack before their fifth birthday, 80% (1869) were free of wheeze at 10 years; only 8% of children who had just one whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
1
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 13 publications
5
38
1
2
Order By: Relevance
“…The Tuscon cohort also demonstrated similar associations, in that children with persistent wheezing were more likely to have wheezed often or very often when compared to those with transient wheeze [6]. Similar observations have been made in the Avon cohort, in that the more frequent attacks children had in infancy, the less likely they were to be symptom-free at 10 years [41]. Similar features have been reported for persistence into adulthood [12,15,19,60], and the oldest reported long-term follow-up study also concluded that severe childhood asthma predisposed to chronic persistent adult disease [34].…”
Section: Severity and Frequency Of Episodessupporting
confidence: 69%
See 1 more Smart Citation
“…The Tuscon cohort also demonstrated similar associations, in that children with persistent wheezing were more likely to have wheezed often or very often when compared to those with transient wheeze [6]. Similar observations have been made in the Avon cohort, in that the more frequent attacks children had in infancy, the less likely they were to be symptom-free at 10 years [41]. Similar features have been reported for persistence into adulthood [12,15,19,60], and the oldest reported long-term follow-up study also concluded that severe childhood asthma predisposed to chronic persistent adult disease [34].…”
Section: Severity and Frequency Of Episodessupporting
confidence: 69%
“…The Avon (UK) birth cohort has also shown that, at 9 years, children whose first attack was in infancy had a better prognosis than those with onset in the 2nd year of life [41]. In pre-school children and after adjustment for the effect of sex, the cumulative prevalence of doctor-diagnosed asthma increases with age of presentation, the estimated multiplicative increase being 1.27 (1.12 to 1.45) for each additional year of age [29].…”
Section: Age Of Onsetmentioning
confidence: 99%
“…The serum concetitratioti of IgE is sigtiificatitly elevated in most patients with allergic diseases such as extrinsic asthma, hay fever and atopic diseases. It is well known that many young children with the clinical pattern of viral associated wheeze will soon outgrow their symptoms, whereas a smaller number go on to develop more classical atopic asthma [15,16]. The differences in eosinophil numbers we found between AA and YAW are unlikely to be due to the For comparative purposes the data from children with viral associated wheeze has also been included.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, whilst wheezing in infancy is common, it appears to have a favourable prognosis, since the majority of children who wheeze in early childhood are free of symptoms by adolescence or early adulthood [9,[23][24][25]. At present, it is not understood why wheezing illness persists in some children, when in most it resolves spontaneously.…”
mentioning
confidence: 99%